2011
DOI: 10.1016/j.watres.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic transformation of humic acid during photoelectrocatalysis process and its subsequent disinfection byproduct formation potential

Abstract: Disinfection byproduct formation potential Structure variationFunctional groups a b s t r a c tIn this study, degradation of humic acid (HA) via photoelectrocatalysis (PEC) process and corresponding disinfection byproduct formation potential (DBPFP) were investigated.Particularly, structure variation and subsequent DBPFP of HA during PEC treatment were correlated. The PEC process was found to be effective in reducing dissolved organic carbon concentration by 75.0% and UV absorbance at 254 nm by 92.0%. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…In the UV-chlorine processes, the formation of more OH inhibits the incorporation of chlorine into HA due to the non-selectivity of OH oxidation, leading to lower TCM formation. This indicates that OH radicals are prone to attack precursors such as those with unsaturated CeC bonds, conjugated double bonds and aromatic groups, because phenolic hydroxyl and conjugated double bonds are primarily responsible for TCM and TCAA formation according to previous works (Li et al, 2011;Tian et al, 2013).…”
Section: Formation Of Dbps During Uv-chlorine Processesmentioning
confidence: 73%
See 1 more Smart Citation
“…In the UV-chlorine processes, the formation of more OH inhibits the incorporation of chlorine into HA due to the non-selectivity of OH oxidation, leading to lower TCM formation. This indicates that OH radicals are prone to attack precursors such as those with unsaturated CeC bonds, conjugated double bonds and aromatic groups, because phenolic hydroxyl and conjugated double bonds are primarily responsible for TCM and TCAA formation according to previous works (Li et al, 2011;Tian et al, 2013).…”
Section: Formation Of Dbps During Uv-chlorine Processesmentioning
confidence: 73%
“…However, a higher amount of DCAA was formed in the former condition, while more TCAA was formed in the latter. Some studies have shown that the DCAA precursor is mainly compounds with carboxyl and alcohol hydroxyl groups (Li et al, 2011), while the TCAA precursor is mainly those with phenolic hydroxyl and conjugated double bonds. Based on the transformation of HA in UVchlorine and chlorine, carboxyl and alcohol hydroxyl intermediates are predominant, leading to higher DCAA formation for UV-chlorine treatment, while phenolic hydroxyl and conjugated double bonds are dominant in intermediates, leading to higher TCAA formation in chlorination.…”
Section: Formation Of Dbps During Uv-chlorine Processesmentioning
confidence: 99%
“…Tran et al reported that the Ho fraction generally contained a large proportion of aromatic structures [25]. However, the Hi fraction contained many aliphatic carbon and nitrogenous compounds [26]. Thus, SUVA appeared to be a better indicator for the reactivity of the compounds that comprise aquatic humic substances than for the DOC present in the whole water samples.…”
Section: The Relationship Between Suva and Dbpfp/docmentioning
confidence: 99%
“…HA molecules are not only a major source of foulant during ultrafiltration process, but also can compete for adsorption sites with target contaminants during activated carbon adsorption to decrease the pollutant removal efficiency [10][11][12][13]. They can also react with chlorine during drinking water treatment processes to produce potentially carcinogenic such as trihalomethanes and haloacetic acids [14][15][16][17]. Activated carbon adsorption, coagulation, electro-coagulation, and biosorption have been widely used for the removal of HA [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%